Epidermolysis Bullosa in Spain: A Qualitative Analysis of Its Social Impact on Families With Diagnosed Minors - Juan Manuel Martínez‐Ripoll; Marta García‐Domingo; Yolanda María de laFuente Robles (Wiley, 2024)
Abstract Background Epidermolysis bullosa (EB) comprises a group of rare types of genodermatoses characterized by extreme mucocutaneous fragility, leading to blistering and/or erosions, even with minimal trauma. Continuous care through wound management is an integral part of daily life for the families and individuals affected. The aim of this study was to assess the social reality and impacts on families of having minor members diagnosed with EB in Spain. Methods A qualitative methodology was employed, utilizing four focus groups entailing participation by 24 parents (19 mothers and five fathers) of minors diagnosed with EB in Spain. Results Negative impacts on the family nucleus were evident in four priority areas of analysis: sociorelational, economic‐labour, physical and psychoemotional, with significant differences observed based on the severity of the symptoms. Conclusion Impacts on the family nucleus are noticeable from birth, influencing all other daily life routines and complicating family planning and organization. There is an imperative need to enhance the availability of sociohealth resources and to adopt an interdisciplinary approach to address their biopsychosocial needs. Patient or Public Contribution The active participation of relatives of minors diagnosed with Epidermolysis Bullosa (EB) is invaluable to sociohealth professionals, legislators and researchers. A team member conducts their professional activities at DEBRA España (national patient association dedicated to enhancing the quality of life for individuals with EB and their families), actively engaging in all study phases.